Caregivers' Barriers to Facilitating Medication Adherence in Adolescents/Young Adults With Solid Organ Transplants: Measure Development and Validation. (6th May 2020) - Cushman, Grace K; Rich, Kristin Loiselle; Rea, Kelly E; Quast, Lauren F; Stolz, Mary Gray; Gutierrez-Colina, Ana M; Eaton, Cyd K; Lee, Jennifer L; Mee, Laura L; George, Roshan; Blount, Ronald L
Abstract: Objective: To evaluate the factor structure, validity, and reliability of the Caregiver Medication Barriers to Adherence Scale (CMBAS), which assesses caregivers' barriers to facilitating medication adherence in adolescent and young adults (AYAs) with solid organ transplants. Methods: The sample included 93 caregivers of AYAs ages 12–22 years who received a liver, kidney, or heart transplant. Caregivers completed the CMBAS and surveys to assess its validity, including internalizing symptoms, personality traits (i.e., neuroticism, conscientiousness), and AYAs' nonadherence to immunosuppressant medications. AYA nonadherence to tacrolimus was objectively assessed via the Medication Level Variability Index (MLVI). Results: Confirmatory factor analyses of the CMBAS revealed a two-factor model: Caregiver Emotional Distress and Caregiver Cognitive Burden/Responsibility. Higher CMBAS scores were related to higher levels of caregiver internalizing symptoms ( r s = .28 to .30), neuroticism ( r = .27), and caregiver proxy-reported immunosuppressant nonadherence ( r = .27), as well as lower levels of caregiver conscientiousness ( rs = −.25 to −.26). The CMBAS was not associated with the MLVI ( r s = −.13 to −.16). Conclusions: The CMBAS demonstrated reliability and validity for caregivers of AYAs with solid organ transplants. Findings support the use of the CMBAS as a brief clinical screening tool to identify caregivers' barriers to facilitating AYA medication adherence.